Development of quaternary blended high performance concrete made with high reactivity metakaolin - Srinivasa Reddy, V; Nirmala, R (International Journal of Engineering and Technology, 2018)
In the last three decades, supplementary cementitious materials such as fly ash, silica fume and ground granulated blast furnace slag have been judiciously utilized as cement replacement materials as these can significantly enhance the strength and durability characteristics of concrete in comparison with ordinary Portland cement (OPC) alone. Hence, high-performance concretes can be produced at lower water/powder ratios by incorporating these supplementary materials. One of the main objectives of the present research work was to investigate synergistic action of binary, ternary and quaternary blended high strength grade (M80) concretes on its compressive strength. For blended high strength grade (M80) concrete mixes the optimum combinations are: Binary blend (95%OPC +5% FA, 95%OPC +5% MS and 95%OPC +5%MK), ternary blend (65%OPC+20%FA+15%MS) and quaternary blend (50%OPC+28%FA+11%MS+11%MK). Use of metakaolin in fly ash based blended concretes enhances compressive strength significantly and  found to be cost effective in terms of less cement usage, increased usage of fly ash and also plays a major role in early strength development  of fly ash based blended concrete.